Performance Analysis of Signal Space Diversity with Transmit Antenna Selection and Maximal Ratio Combining - Ozyurt, Serdar; Kucur, Oğuz (IEEE, 2017)
A multiple input multiple output communication system with transmit antenna selection and maximal ratio combining is combined with signal space diversity and its performance is investigated by means of statistical methods. To this end, signal constellation rotation angles minimizing error probability are obtained for phase shift keying modulation under Rayleigh fading channel when the modulation level is two and four. The positive effect of proper rotation angles on the system error performance is illustrated.
25th Signal Processing and Communications Applications Conference (SIU) -- MAY 15-18, 2017 -- Antalya, TURKEY
Keywords: Multiple input multiple output; transmit antenna selection; maximal ratio combining; signal space diversity